MENINGKATKAN HASIL BELAJAR OPERASI BENTUK ALJABAR DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) PADA SISWA KELAS VII SMP - Unpapar, Vivi Rosalia; Laamena, Christina M; Huwaa, Novalin C (Program Studi Pendidikan Matematika (Kampus Kab. Maluku Barat Daya) Universitas Pattimura, 2022)
This study aims to determine the improvement of student learning outcomes on the material of algebraic operations using the Think Pair Share learning model. The subjects in this study were all seventh grade students of SMP PGRI Kaiwatu with a total of 14 students. This research is a classroom action research with the teacher acting as a teacher and lasts for 2 cycles. Data collection was carried out using tests and observations. Data analysis used quantitative analysis and qualitative analysis. The results of the analysis showed that there was an increase in student learning outcomes from the first cycle, 5 students who achieved the KKM 70 or 35.71% and those who did not complete 9 students or 64.29%, to the second cycle 11 students obtained the KKM 70 or 78.57% and 3 students who did not complete or 21.43%. From the results obtained, the cooperative learning model of the think pair share type can improve student learning outcomes in the algebraic form of operation material.